Protective Effect of Benidipine Against Sodium Azide-Induced Cell Death in Cultured Neonatal Rat Cardiac Myocytes - Koji Inomata; Hiroyuki Tanaka (Elsevier, 2003)
ABSTRACT: We investigated the effect of benidipine, a calcium antagonist, against sodium azide (NaN3)-induced cell death in cultured neonatal rat cardiac myocytes with increase of LDH release, depletion of cellular ATP contents, and collapse of mitochondrial membrane potential (ΔΨ) as indicators. Cells were treated with 1 mmol/L NaN3 for 18 h. Benidipine concentration-dependently inhibited NaN3-induced cell death. The protective effect of benidipine was compared with those of amlodipine, nifedipine, candesartan, and captopril. Calcium antagonists exhibited a protective effect and the IC50 values of benidipine, amlodipine, and nifedipine were 0.65, 90, and 65 nmol/L, respectively. NaN3-induced cell death was inhibited completely with the calpain inhibitor. It was considered that the sustained elevation of [Ca2+]i might be implicated in NaN3-induced cell death. Benidipine, moreover, concentration-dependently preserved cellular ATP contents and maintained ΔΨ the extent of the control level. In conclusion, benidipine exhibited the protective effect at an approximately 100-fold lower concentration than those of amlodipine and nifedipine in the NaN3-induced cardiac cell death model. It was considered that both the inhibition of Ca2+ influx and the preservation of cellular ATP contents might play an important role in the protective effect of benidipine.